Agility counts. (Economist, 2001)
Part of a special section on technological innovations. In order to develop software that is relevant to customers' changing needs, 17 leading software gurus have produced a “Manifesto for Agile Software Development.” Agile programming is the culmination of many faddish ideas for producing software more efficiently, and what lies behind it is an emphasis on the benefits of team work in a business plagued by solo operators. The manifesto presents the outcome of many successful team-oriented methodologies, and could be applicable for innovation groups who operate outside the field of software development. Something common to all approaches to agile programming is an increased emphasis on personal communication and programmer morale. In addition, the signatories to the manifesto believe in rapid and numerous releases of partial programming solutions so that customers can react along the way to a final product.